Considering the fragility index in reporting trials on diverticular disease - Andrew P. Zbar; Nir Horesh (Exploration of Digestive Diseases)
The changing management paradigm of acute complicated diverticulitis and the elective indications for surgery have evolved in the last decade based on reported evidence-based data. Recently, it has been demonstrated that randomized controlled trials (RCTs), the highest trial format in the hierarchy of evidence-based reporting, suffer from a ‘crisis of replicability’. The development of a fragility index (FI) quantitatively defines the robustness of an RCT by shifting the number of participants in a trial into a different binary group in an effort to influence reported statistical significance (the lower the FI the greater the study fragility). The only available report on FI in diverticular management showed that in an eclectic range of RCT’s comparing intervention and non-intervention, two-thirds of the studies had an FI ≤ 1 where statistical recalculation using Fisher’s Exact test rendered one-quarter of previously positive studies non-significant. Comparisons between studies and units are still dependent upon sample sizes and the numbers lost to follow-up even when some of the FI progeny (including a reverse FI, a fragility quotient dividing the FI by the sample size, or other incidence or generalized FI metrics) are utilized in assessment. Future analyses need to define all comparisons rather than cherry-picking examples where a p value approaches significance. Despite the fact that no FI value defines the strength of a RCT, its use attempts to link the reported p value with the sample size and the statistical power of the study. Positive findings in diverticular trials are then considered not so much definitive as rather provocateurs encouraging further similarly designed studies in different environments. Minimizing patient loss in treatment arms and reporting the reasons for drop-out, strictly adhering to randomization, consistent blinding, and group allocation concealment can all improve the logistical running of an RCT initially designed to evaluate some potentially important new treatment.